Kedudukan Hukum antara Pengguna Jasa dan Financial Planner dalam IKD Financial Planner - Duhita Pramesi Tyaskinasih (Faculty of Law, Universitas Airlangga, 2023)
AbstractDigital Financial Innovation or IKD (a new name for fintech by the Financial Services Authority/OJK) is an activity to innovate business processes, business models, and financial instruments that can provide new added value in the financial services sector and in its implementation in-volves the digital ecosystem. IKD Financial Planner is one of IKD’s groups based on a digital financial planning business model by accredited financial planners who offer their services through a digital platform. This study will discuss regarding an agreement of Finansialku, one of the IKD Financial Planner platforms authorized by the OJK. In the transaction, the main binding agreement between the Finansialku team and its service users is the Application User Agreement. This study aims to identify the legal standing between users and financial planners on IKD Financial Planner Finansialku ecosystems. This study concludes that in the main agreement the legal subjects who are bound and have legal standing are Members (service users) and IKD (service providers, in the form of limited liability company), without the involvement of financial planners.Keywords: Digital Financial Innovation; Fintech; Financial Planner, Digital Financial Planner. AbstrakInovasi Keuangan Digital atau IKD adalah aktivitas pembaruan proses bisnis, model bisnis, dan instrumen keuangan yang dapat memberikan nilai tambah baru di sektor jasa keuangan dan dalam penyelenggaraannya melibatkan ekosistem digital. Penelitian ini membahas perjanjian dari Finansialku, salah satu plat-form IKD Financial Planner yang diakui oleh OJK. Dalam transaksinya, perjanjian utama yang mengikat antara tim Finansialku dan pengguna jasanya adalah Perjanjian Pengguna Aplikasi. Penelitian ini bertujuan untuk mengidentifikasi kedudukan hukum antara pengguna jasa dan financial planner dalam ekosistem IKD Financial Planner Finansialku. Penelitian ini menyimpulkan bahwa dalam perjanjian utamanya subyek-subyek hukum yang terikat dan memiliki kedudukan hukum adalah Ang-gota (pengguna jasa) dan IKD (pemberi jasa, berbentuk Perseroan Terbatas), tanpa melibatnya perencana keuangan.Kata Kunci: Inovasi Keuangan Digital; Fintech; Perencana Keuangan; Perencana Keuangan Digital